2015
DOI: 10.1021/acs.oprd.5b00010
|View full text |Cite
|
Sign up to set email alerts
|

Nonprecious Metals Catalyzing Hydroamination and C–N Coupling Reactions

Abstract: This review highlights the recent achievements in replacing precious-metal-based catalysts with nonpreciousmetal-based catalysts in two important syntheses: hydroamination and C−N coupling reactions. The reported improvements are discussed in direct relation to the nature of the ligands, catalyst preparation methods, and the selection of other additives. Syntheses using ligand-free catalysts are also analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 273 publications
2
37
0
Order By: Relevance
“…Hydroamination of alkenes and alkynes is ap owerful strategy for the formation of CÀNb onds.Such processes are complementary to aza-Heck reactions because the product is generated at alower unsaturation level. Avariety of strategies have emerged for effecting alkene and alkyne hydroaminations,i ncluding metal- [198][199][200][201][202][203][204][205][206][207][208][209][210][211] and Bronsted acid catalyzed [212][213][214] methods,r adical-mediated processes [215][216][217][218][219] and pericyclic-based methods. [220,221] Conventional hydroamination protocols are designed to enable the addition of an amine NÀHbond across an alkene or alkyne p-bond.…”
Section: Copper-catalyzed Hydroaminationmentioning
confidence: 99%
“…Hydroamination of alkenes and alkynes is ap owerful strategy for the formation of CÀNb onds.Such processes are complementary to aza-Heck reactions because the product is generated at alower unsaturation level. Avariety of strategies have emerged for effecting alkene and alkyne hydroaminations,i ncluding metal- [198][199][200][201][202][203][204][205][206][207][208][209][210][211] and Bronsted acid catalyzed [212][213][214] methods,r adical-mediated processes [215][216][217][218][219] and pericyclic-based methods. [220,221] Conventional hydroamination protocols are designed to enable the addition of an amine NÀHbond across an alkene or alkyne p-bond.…”
Section: Copper-catalyzed Hydroaminationmentioning
confidence: 99%
“…Despite these advances, engagement of benzylamines in their deprotonative benzylic alkylation with styrenes remains elusive. When primary and secondary amines are employed, the base‐mediated deprotonation occurs on the amine site and the resulting amide anions show the propensity to undergo hydroamination [20–24] . Interestingly, Hultzsch observed that the reaction of benzylamine ( 4 ) and styrene ( 5 ) catalyzed by KN(SiMe 3 ) 2 and TMEDA affords not only hydroamination products 6 and 6′ , but also 1,3‐diphenylpropylamine ( 7 ) as a minor co‐product through hydroalkylation of styrene ( 5 ) ( Scheme 3).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the properties of the catalyst, this reaction can afford either the Markovnikov or anti-Markovnikov products ( Figure 2) [52][53][54][55][56][57][58]. Furthermore, a few Rh species have been reported as excellent catalysts for this process [59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%